A comparative study between limb-salvage and amputation for treating osteosarcoma - Li, Xiaojuan (J Bone Oncol, 2016)
PURPOSE: Osteosarcoma is an aggressive malignant neoplasm, and conflicting findings have been reported on the survival and function recovery in osteosarcoma patients experiencing limb salvage or amputation. In the present study, we compared clinical outcomes regarding limb salvage surgery vs. amputation for osteosarcoma patients by a meta-analysis. METHOD: Literature search was conducted in CNKI, Medline, Embase, the Cochrane Database, and Web of Sciences, and the quality of included studies was evaluated based on Newcastle-Ottawa scale quality assessment. Odds ratio and 95% confidence interval of the local recurrence, 5-year overall survival, and metastasis occurrence were calculated. RESULTS: 17 articles were included according to selection criteria. There were 1343 patients in total derived from these studies. Our result showed that there was no significant difference between limb salvage surgery and amputation with respect to local recurrence, and patients with limb salvage surgery had a higher 5-year overall survival, and a lower metastasis occurrence. CONCLUSIONS: The present study provided more comprehensive evidences to support limb salvage surgery as an optimal treatment of osteosarcoma patients.